PSYCHO-SOCIAL PRE-RETIREMENT PLANS OF LECTURERS IN PUBLIC UNIVERSITIES IN RIVERS STATE, NIGERIA. - Amini-Philip, Chinyere; Kinanee, Nadum Nekabari (Advances in Social Sciences Research Journal, 2019)
Abstract The study investigated lecturers’ psycho-social pre-retirement plans in public universities in Rivers State, Nigeria. Two (2) research questions were formulated and answered while two (2) hypotheses were tested at 0.05alpha level. The study adopted a descriptive survey research design. The population of the study consisted of all the 2330 lecturers in the three public universities in Rivers State. As at the time of this study, each of the universities has the following population breakdown respectively: University of Port Harcourt (UNIPORT) 1500, Rivers State University (RSU) 556, Ignatius Ajuru University of Education (IAUOE) 274 making a total of 2330 lecturers from the three (3) public universities in Rivers State. (Source: Registry Department of the various institutions 2017). A sample size of 932 was used. The sample size was drawn using simple random sampling technique from the three universities in Rivers State. The instrument for the study was titled “Lecturers Psycho-Social Pre-Retirement Plans Scale” (LPSPRPS). Simple percentage was used to answer the research questions while Chi-Square statistics was used to test the null hypotheses at 0.05 alpha level. It was found among others that 46% of the lecturers agree that they have financial plans while 54% disagree. It was recommended among others that Pre-Retirement Guidance and Counselling centres should be established in university communities where lecturers who have emotional problems can go and seek help from counsellors.